(untitled) (ACME, 2024)
The study of lexical borrowings from Italian to French has produced a large body of literature focusing mainly on France. But what about Italianisms in other geographical varieties of French? The development of differential lexicography, which describes lexical units specific to the various French-speaking areas, has led to the creation of a large corpus which now makes it possible to direct this research towards extra-hexagonal vocabularies. The Quebec domain is of particular interest, as we now have a variety of lexicographical descriptions integrating differential, descriptive and terminological approaches. An analysis of the semantic domain relating to food in the GDT will enable us to examine the innovative elements that Italian brings to Quebec French and the assimilation strategies attested in this variety of language. This research will also allow us to reflect on the ways in which Italian can still prove to be an enriching language for French, particularly as it expands outside France.